Examining Cross-Cultural Clues as to Globalization and Iran's Culture in an International ELT Book Series - American English File - Ziaei, Sima (Mediterranean Journal of Social Sciences, 2012)
This study aims to investigate the cross-cultural issues in four volumes of an English textbook- American English File.For the aim of this study the different countries mentioned in the book were highlighted and classified based on different aspectsof culture. This study believes in global English and intends to discover the extent to which these books consider this issue. Theresults suggest the UK and the USA were the most frequent mentioned countries in the reading texts. Iran as an Asian countryhad no room in this book and Japan was the most frequent Asian country.